2009
DOI: 10.1097/sla.0b013e3181b2468b
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome by Growth Rate of Locally Recurrent Retroperitoneal Liposarcoma

Abstract: Objective To identify the prognostic variables that predict disease-specific survival and second local recurrence-free survival in patients with recurrent retroperitoneal liposarcoma so as to guide clinical management. Summary Background Data Local recurrence following complete resection of primary retroperitoneal liposarcoma is a common clinical problem that frequently leads to morbidity and mortality. Factors that determine survival in patients with a local recurrence after complete resection of the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
143
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 21 publications
8
143
0
Order By: Relevance
“…For patients with recurrence who cannot undergo complete resection, the aim of treatment is to attenuate symptoms, remove oppression of the surrounding organs and obstruction of the tumor, maintain visceral function, extend survival time and improve the quality of life. A previous study indicated that if the speed of growth of a recurrent tumor is >0.9 cm per month, multiple surgeries do not improve the survival rate (50).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with recurrence who cannot undergo complete resection, the aim of treatment is to attenuate symptoms, remove oppression of the surrounding organs and obstruction of the tumor, maintain visceral function, extend survival time and improve the quality of life. A previous study indicated that if the speed of growth of a recurrent tumor is >0.9 cm per month, multiple surgeries do not improve the survival rate (50).…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data to guide the management of locally recurrent retroperitoneal liposarcoma following complete resection of the primary [11]. The efficacy of chemotherapy has not been demonstrated in any hitherto published study.…”
Section: Discussionmentioning
confidence: 99%
“…Local recurrence following complete resection of primary retroperitoneal liposarcoma is common with 50% of well-differentiated and 80% of dedifferentiated tumors recurring within 5 years, and most patients who die of retroperitoneal soft tissue sarcoma die from the effects of local recurrence [11]. There is limited data to guide the management of locally recurrent retroperitoneal liposarcoma following complete resection of the primary [11].…”
Section: Discussionmentioning
confidence: 99%
“…Palliative surgery may have short-term symptomatic benefit, but this rarely lasts longer than 90 days. 50 …”
Section: Sts Of the Retroperitoneummentioning
confidence: 99%
“…Surgery for locoregional recurrence may be offered on an individual basis, especially to patients who are affected by low-grade liposarcoma, those who have a long disease-free interval between initial resection and subsequent recurrence, 50 or those who experience a response to therapy. There is little benefit to incomplete resections for recurrent disease with the possible exception of patients who have well differentiated liposarcoma.…”
Section: Sts Of the Retroperitoneummentioning
confidence: 99%